Successful management of a severe anti-M alloimmunization during pregnancy. (October 2017) - Hubinont, Corinne; Delens, Gilda; Vanalbada De Haan Hettema, Julie; Lambert, Catherine; Debauche, Christian; Biard, Jean-Marc
Abstract: We report the successful outcome of a patient with anti-M antibodies with a previous history of severe hemolysis of erythrocytes. Serial plasma exchange from the first trimester combined with ultrasound monitoring of the fetal middle cerebral artery blood velocity was implemented. This management allowed a favorable pregnancy outcome of an infant born by an elective caesarean section at 32 weeks 6/7 with a normal Apgar score at 8/9/10. The other therapeutic alternatives such as intravenous immunoglobulin and in utero fetal blood transfusions are discussed.